EXPLORING THE MODERATING ROLE OF AUDIT QUALITY IN THE IMPACT OF CORPORATE GOVERNANCE ON THE INVESTMENT EFFICIENCY OF THE COMPANIES LISTED IN TEHRAN STOCK EXCHANGE - Hosein Moradi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Regarding the increased competition in trade, firms need to rely on appropriate timely investments to survive. Because of the developments in the contemporary world, especially in the developing countries, these countries need appropriate solutions to make better use of their facilities to solve their economic problems. One of the important factors in solving the economic issues of the countries is to expand and develop investment. However, it is not sufficient by itself; due to the limited financial resources, in addition to investment development, increasing the investment efficiency is an important issue as well. Hence, the present study attempted to explore the impact of the corporate governance mechanism on investment efficiency as well as the moderating role of audit quality in this relationship. It is applied descriptive-correlational research. In other words, this study explored the relationship and correlation between variables through regression. To achieve the above purpose, three hypotheses were developed. For hypothesis testing, a sample of 108 companies listed in the Tehran Stock Exchange from 2013 to 2019 was selected. The multivariate regression model based on panel data was used for hypothesis testing. The results of this research indicate that there is a significantly positive relationship between corporate governance and investment efficiency with the moderating role of audit quality.